The Importance of Forming the National Self-Consciousness of Schoolchildren - Uteeva, Kundyz (Pedagogy and Psychology, 2022)
Today, the formation of an effective national consciousness within the walls of the school is a way to raise the country, spiritual renewal of our society. The result of such education is determined by how sincere the student is in his creative path. The result of the student’s work on patriotic education is measured by his contribution to the prosperity of his native land, his homeland, the ability to combine personal and public interest, the teacher’s motivation and readiness to fulfill his civic and patriotic duties to students. The main directions of the educational sphere, ways to organize them, types of work with parents, ways to instill patriotic education in students are considered in the creative work.